Die Rechtsstellung des angemeldeten Verbrauchers in der Musterfeststellungsklage - E. Oehmig, Adrian (Schriften zum Prozess- und Verfahrensrecht, 2021)
Subject of the thesis is primarily the constitutional admissibility of the binding effect pursuant to Section 613 of the German Code of Civil Procedure (ZPO), in particular with regard to the legal hearing of registered consumers. Under this aspect the applicability of the procedural institutes of the change of action and the counterclaim in the model declaratory action (Musterfeststellungsklage) is examined in the further course, which according to the opinion of the author require a very restrictive application in the proceedings of the qualified institution. Lastly, the highly sensitive issue of the liability of the qualified institution for inadequate conduct of proceedings in the model declaratory action is addressed.